Functional analysis of cilia and ciliated epithelial ultrastructure in healthy children and young adults. Issue 4 (1st April 2003) - Chilvers, M A; Rutman, A; O'Callaghan, C
Abstract : Background: There are very few data on normal ciliary beat frequency, beat pattern, and ultrastructure in healthy children and adults. A study was undertaken to define ciliary structure, beat frequency and beat pattern in a healthy paediatric and young adult population. Methods: Ciliated epithelial samples were obtained from 76 children and adult volunteers aged 6 months to 43 years by brushing the inferior nasal turbinate. Beating cilia were recorded using a digital high speed video camera which allowed analysis of ciliary beat pattern and beat frequency. Tissue was fixed for transmission electron microscopy. Results: The mean ciliary beat frequency for the paediatric population (12.8 Hz (95% CI 12.3 to 13.3)) was higher than for the adult group (11.5 Hz (95% CI 10.3 to 12.7 Hz), p<0.01, t test); 10% (range 6–24%) of ciliated edges were found to have areas of dyskinetically beating cilia. All samples had evidence of mild epithelial damage. This reflected changes found in all measurements used for assessment of epithelial damage. Ciliary ultrastructural defects were found in less than 5% of cilia. Conclusion: Normal age related reference ranges have been established for ciliary structure and beat frequency. In a healthy population localised epithelial damage may be present causing areas of ciliary dyskinesia.